Optimalisasi Laba Produksi Pangan Menggunakan Program Linier Dengan Metode Simpleks dan POM-QM for Windows di Warung Cek Nur - Rina Gebryella Gultom; Rosiana Claudia Br Gultom; Suvriadi Panggabean (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
Linear programming is one of several methods of maximizing or minimizing an objective function to create an optimal solution. However, an efficient method is needed to perform calculations. In this research, the manual simplex method was used to maximize profits from the sale of penyet chicken, geprek chicken and halibut chicken in one of the MSME businesses in the city of Medan. Apart from that, an analysis tool was also used in the form of an application called POM-QM for Windows to verify the calculation results manually. In this research, 3 variables and 7 obstacles were identified which were resolved using the simplex method which means a maximum profit of IDR 2,330,000 per day with an increase of IDR 1,194,000.